SUBSIDENCE ANALYSIS AND THERMAL HISTORY OF THE SOUTH WESTERN PART OF THE MALAY BASIN - ,, MUHAMMAD HASSAAN (2015)
The Malay Basin is located in the continental core of Sunda shelf which is affected by active subduction of pacific and Indo-Australian plates. Subsidence and thermal history analysis of ten (10) wells are carried out in the south western part (Tenggol Arch and basinal side) of the Malay basin to understand the Cenozoic development. The south western part of the Malay Basin, structurally consist of normal faults, horst and graben geometry. Tenggol fault is the boundary fault between the SW Malay Basin (basinal side) and Tenggol arch. It penetrated through all Cenozoic sediments. Analysis of tectonic subsidence curves shows that the basinal side is more active than the tenggol arch which could be due to the normal faults movement. Cenozoic development initiated with Unit M & L (Oligocene / 33.9-25.2 Ma) deposition and activation of Tenggol fault on the basinal side, whereas these units are not found on the Tenggol arch.